Current methods and applications in computational protein design for food industry. Issue 19 (27th October 2020) - Chen, Qiuming; Xiao, Yaqin; Zhang, Wenli; Mu, Wanmeng
Abstract: Computational tools for enzyme engineering can readily be used in a broad range of food industrial applications. However, there are too many choices when the enzymologists try to solve their own problems computationally, especially when their studies need to be carried out with a combination of tools. The correct choice of methods requires a broad understanding of the knowledge framework. Therefore, we present a comprehensive overview of the current computational tools and basic principles for enzyme design. The tools can be classified into several groups, including bioinformatics approaches and the calculation methods based on static systems and dynamics systems. In addition, we also provide some successful examples in the food industrial applications to show that the modern tools can dramatically reduce the experimental effort and can help us better understand the catalytic mechanism of food enzymes.